Making a Website as Brand Image at SMPN 3 Kutorejo, Mojokerto Regency - Rosyida Nurul Anwar; Yuyun Iqmatul Amalia; Arlina Puspita Sari Safitri; Yulia Andriana (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Education has beginning to see substantial changes as a result of the advancement of information technology. The school's brand image shows its ability to satisfy stakeholder demands, earn confidence, and deliver high-quality services. This community service project seeks to assist schools in communicating information and projecting a positive image and professionalism to the larger community. SMPN 3 Kutorejo, Mojokerto Regency is the activity's partner. The implementation technique finds and resolves partner difficulties through technological adaption, problem-solving, mentorship, and assessment. The website offers a variety of information about the school, including articles on school events, student lists, contact information for faculty and staff, and key announcements. Having a school website aided in the educational realization of a Global Indonesia.